Study of thyroid hormone profile in women presenting with abnormal uterine bleeding attending gynaecology out patient department, tertiary care centre Raipur - Jaiswal, Jyoti; Naik, Smrity; Yadav, Shweta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Menstrual disorders pose a huge burden on genecology OPD, accounting for 10-30% of attendance. Women with HMB have a significant impact on physical, emotional, social, professional and family perspectives which leads to decrease in work productivity. Thyroid gland is closely linked with the process of ovarian maturation and endometrial hyperplasia, its dysfunction also causes abnormal uterine bleeding (AUB). Methods: This was an observational cross-sectional study performed at Pt J. N. M. medical college associated with Dr. B.R.A.M. hospital Raipur (C.G.) between 1st January 2020 to 31st December 2020. Total 100 cases between 18-45 years of age with AUB were included routine investigations and ultrasonography done. Results: Majority of AUB cases belong to the more than 39 years (46%), 41% were multiparous. The 20% cases of AUB have hypothyroidism, 2% have subclinical hypothyroidism, 7% have hyperthyroidism. Commonest pattern of bleeding was heavy menstrual bleeding (52%). They 37% cases had leiomyoma of uterus, 17% cases had adenomyosis, and 14% cases had ovulatory dysfunction. The 12 cases having hypothyroidism and 3 cases having hyperthyroidism presented with heavy and prolonged bleeding. Conclusions: There is significant increase in thyroid disorders in cases with AUB as compared to general population. More than one fourth of cases of AUB were having thyroid disorder. Hypothyroidism is 3 times more common than hyperthyroidism. It is suggested that women of any age having AUB should be offered thyroid profile test to detect thyroid disorders. Early detection can provide early diagnosis and treatment.